Perfil de agravos à saúde entre bombeiros militares no estado do Pará - FONSECA, Rodrigo Barros (2023)
Introduction: firefighters are exposed to factors responsible for triggering health problems. Objectives: to identify the main health injuries of the Firefighters, as well as to relate these diseases to the professional activity (operational or administrative) and to identify risk factors associated to these diseases. Methods: an observational cross-sectional study with 274 firefighters in active service was conducted; the data collection was made from December 2020 to June 2021. Results: the injuries that prevailed were musculoskeletal (70.4%), infectious and parasite (62.8%). We verified a significant correlation between administrative activities and musculoskeletal injuries and between operational activities and work accidents occurrences. We identified many risk factors related to the occurrence of injuries in the studied population, such as repetitive movements, stressing working environment, age, lack of regular physical activity, smoking and altered sleep pattern. Conclusions: the firefighters suffer from many injuries, especially those to the musculoskeletal system and those that are related to infectious agents and parasites. The acknowledge risk factors is fundamental to elaborate prevention measures and health promotion for this population.